DEVELOPMENT OF SOCIO-EMOTIONAL SKILLS IN THE BASIC EDUCATION SCHOOL ENVIRONMENT: A RELEVANT REFLECTION - Malta, Yêda Sá; Soares, Juliana Malta (Seven Editora, 2025)
Competencies are fundamental for the integral development of students and for academic and professional success. In the school context, socio-emotional competencies are essential to promote coexistence, inclusion, and the well-being of students. This article aims to reflect on the importance of socio-emotional competencies in the school environment and strategies to promote the development of these competencies in basic education students. This research is based on the technical procedures of bibliographic research. It highlights the existence of various actions that can be taken by basic education teachers based on mediation criteria that stimulate socio-emotional competencies in the school environment. The results of this research allow us to conclude that there is relevance in addressing socio-emotional competencies in basic education to improve pedagogical action and stimulate teamwork and active reflection among students, thus generating more meaningful learning permeated by student protagonism.DOI: https://doi.org/10.56238/sevened2025.038-077